Aplikasi metode quality function deployment (QFD) dalam perancangan produk tempoyak - Alavia Hardiyanti; Karseno Karseno; Ervina Mela (AGROINTEK, 2022)
Tempoyak is a food that made from fermented durian flesh with the addition of salt. In product development, one of the ways to get products that are in accordance with consumer desires is the Quality Function Deployment (QFD) method. QFDis a design method that can be used to meet customer requirements and evaluate product performance. The research objectives areknowing attributes of consumer requirements for tempoyak products, knowing the technical parameters in the manufacture of tempoyak products, and knowing the priority of consumer requirements, the level of importance and technical parameters in designing tempoyak products. The results showed that there were 17 attributes that consumers wanted, namely sweet-sour taste, yellowish white color, tempoyak aroma, price Rp. 50,000 per kilogram, there is a label on the packaging, the primary color of the transparent packaging, the small package size is 250gram, the jar packaging, the inclusion of the composition, useful for maintaining the digestive system, the inclusion of the expiration date, the inclusion of the halal logo, the inclusion of BPOM, the inclusion of the production date, the inclusion of instructions for storage , inclusion of serving suggestions, and cleanliness of the tempoyak production process. The results also show that there are 8 technical parameters, namely the preparation of raw materials, separation of durian flesh from seeds, mixing of durian meat with salt, fermentation, packaging, labeling, BPOM registration, and MUI halal registration. Attributes of consumer requirements that are of high priority are the inclusion of an expiration date, cleanliness of the tempoyak production process, the inclusion of a halal logo, a label on the packaging, and the inclusion of BPOM. Technical parameters that are of high priority in tempoyak development are labeling, preparation of raw materials, packaging, fermentation, and mixing of durian meat with salt.